MANAJEMEN PARTISIPASI KOMITE SEKOLAH DALAM MENINGKATKAN SARANA DAN PRASARANA DI SDIT CAHAYA SUNNAH CILEUNGSI BOGOR - Khusni Alhan (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2022)
The purpose of this study was to determine the participation of school committees in implementing the management of educational facilities and infrastructure at SDIT Cahaya Sunnah Cileungsi Bogor. This research is a field research (field research) with a qualitative descriptive research type. The subjects of this study were the Head of Madrasah, Deputy Head of Madrasah in the field of educational facilities and infrastructure. The object of this research is the implementation of the management of educational facilities and infrastructure which includes planning, procurement, use, maintenance, inventory and elimination of educational facilities and infrastructure. Methods of data collection obtained from the method of observation, interviews and documentation. The results of the study on school committee participation in the management of educational facilities and infrastructure at SDIT Cahaya Sunnah Cileungsi Bogor, namely: (a) Planning for facilities and infrastructure which is carried out every new school year. (b) Procurement of educational facilities and infrastructure is carried out by adjusting the needs that have been planned. (c) the use of facilities and infrastructure is carried out properly according to their functions. (d) maintenance of facilities and infrastructure is carried out routinely and periodically. (e) an inventory of educational facilities and infrastructure is carried out regularly according to the implementation procedure. (f) the deletion of educational facilities and infrastructure is carried out by collecting data and considering the items to be abolished.